Inovasi Mahasiswa KKN Profesi Dalam Meningkatkan Minat Kunjungan Mahasiswa ke UPT. Perpustakaan Universitas Muhammadiyah Enrekang - Aulia; Fatliani, Nurul; Rina; Hasriani; Allo, Karmila Pare (LESTARI : Jurnal Pengabdian Kepada Masyarakat, 2025)
The innovation of KKN Profesi students aims to increase the interest of students visiting the UPT Library of Muhammadiyah University of Enrekang The method used is a qualitative approach through interviews, observations, and documentation to evaluate the condition of the library and the needs of students. The results of this activity include increasing the collection of digital books in the form of e-books, procuring posters, preparing repositories and activating the library's social media accounts. The conclusion of this study shows that the innovation of KKN Profesi students aims to increase the interest of students visiting the UPT Library of Muhammadiyah University of Enrekang The library is expected to attract student visits and strengthen its role as a learning center. Further involvement of librarians and students is very important to support the development of the library in the future.